Educated [compact disc, unabridged] : a memoir - Westover, Tara (Random House Audio, 2018)
A searing, unforgettable memoir about a young girl who, raised by Mormon survivalists in the mountains of Idaho and forbidden to go to school, defies her family and earns a PhD from Cambridge University.